Extracellular Hyaluronic Acid Influences the Efficacy of EGFR Tyrosine Kinase Inhibitors in a Biomaterial Model of Glioblastoma. Issue 21 (2nd August 2017) - Pedron, Sara; Hanselman, Jacob S.; Schroeder, Mark A.; Sarkaria, Jann N.; Harley, Brendan A. C.
Abstract: 3D biomaterial models have potential to explore the influence of the tumor microenvironment on aberrant signaling pathways and compensatory signals using patient‐derived cells. Glioblastoma (GBM) tumors are highly heterogeneous, with both cell composition and extracellular matrix biophysical factors seen as key regulators of malignant phenotype and treatment outcomes. Amplification, overexpression, and mutation of the epidermal growth factor receptor (EGFR) tyrosine kinase have been identified in 50% of GBM patients. Here, hyaluronic acid (HA) decorated methacrylamide‐functionalized gelatin (GelMA) hydrogels are used to examine the synergies between microenvironmental factors and a model EGFR tyrosine kinase inhibitor (TKI) using patient‐derived xenograft cells. The in vitro behavior of 3 patient‐derived xenografts that reflect a clinically relevant range of EGFR variants is characterized: GBM10 (EGFR, wild type), GBM12 (EGFR+), and GBM6 (EGFRvIII). GelMA hydrogels support xenograft culture; cells remain viable, active, respond to matrix‐immobilized HA, and upregulate genes associated with matrix remodeling and tumor growth. Interestingly, matrix‐immobilized HA alters the response of GBM cells to a model tyrosine kinase inhibitor, erlotinib. While constitutively activated EGFRvIII cells are sensitive to TKI in gelatin hydrogels, hyaluronic acid mediated adhesive signaling interacts with EGFRvIII signaling to increase cell metabolic activity, increase soluble hyaluronic acid synthesis, and modify response to erlotinib exposure. Abstract : This biomaterial tumor model recreates relevant features of the glioblastoma tumor microenvironment, and is used as a valuable tool in the mechanistic studies of tumor development and prediction of tyrosine kinase inhibitors efficacy. Experiments here highlight the importance of extracellular hyaluronic acid in inhibition efficiency of epidermal growth factor receptor by erlotinib.